Possible Hepato-Protective Effects of Sodium Copper Chlorophyllin against Chlorpyrifos Induced Toxicity in Adult Female Rats - alkhazali, Ali Zaid; Abdullah, Asia S.; Moziel, Muhsin S. AL (Journal of Science in Medicine and Life, 2025)
Chlorpyrifos (CP), a widely used pesticide, leaves residues in crops, raising concerns due to oxidative stress and lipid peroxides. Sodium copper chlorophyllin (SCC), a water-soluble derivative of chlorophyll composed of sodium-copper salts, may offer protective effects. This study investigates SCC’s potential to counteract CP-induced liver toxicity in rats and explores its role in reducing pesticide-driven oxidative damage. Thirty adult female albino rats were divided into five groups (6 rats each). Group 1 received distilled water (control), Group 2 was treated with CP (6.7 mg/kg), Group 3 received SCC (50 mg/kg), while Groups 4 and 5 received CP plus SCC at low (50 mg/kg) and high (100 mg/kg) doses respectively. All administered orally daily for six weeks. Blood samples for biochemical analysis, and liver tissues for histopathology were collected after sacrifice. No deaths or changes in appearance were observed. All groups except the CP-only group showed significant weight gain. CP administration caused notable increases in serum liver enzymes (ALT, AST, ALP), while SCC alone did not affect enzyme levels. Co-treatment with CP and SCC (both doses) significantly reduced these enzyme levels compared to CP alone, suggesting a protective effect. Additionally, CP elevated serum malondialdehyde (MDA) and lowered glutathione (GSH) levels, whereas SCC alone had no significant impact on these markers. SCC co-administration reversed these effects, decreasing MDA and increasing GSH levels. Histological findings aligned with the biochemical data. SCC demonstrates a protective role against CP-induced oxidative liver damage. Further research is warranted to validate these findings and clarify the mechanisms involved.